Alcance y límites del principio de jerarquía. Criterios para jerarquizar derechos, valores, bienes y otros elementos - Riofrío, Juan Carlos (2020)
The main aim of this research is to show the true dimension of the hierarchy principle, its scope and its limits. The goal is to overcome the normative vision of this principle, observing how it operates in other juridical elements, as charges, ends, values, goods, principles and rights. A philosophical, speculative and abstract method is used, endorsed with examples from the law of several nations and the international law. As the greatest debate in this field is the hierarchy of rights, viewed skeptically by a big part of the doctrine, this paper focuses on seeing how the hierarchy might work there. The analysis has a tripartite structure: a) exposition of the problem, b) exposition of notions, and c) resolution of the problem using the provided notions. In the first comprises the hierarchy principle, its positive and negative functions, and its conditions and limits, defining the possible hierarchical criteria. Finally, in the last sections, it’s checked whether the mentioned notions and criteria are applicable to the problem of rights and to other elements. After checking it the conclusions are presented.sections the arguments for and against the hierarchy of rights are exposed, andis shown where the problem of hierarchization lies. Then, it’s explained what